Archbishop Ató of Osona: false metropolitans on the Marca Hispanica - Jarrett, J (Böhlau Verlag GmbH & Cie, 2010)
Although in other respects the national scholarship of Catalonia has become sceptical of a 'national' consciousness in the area prior to the end of the Carolingian kingdom in West Francia in 987 to which the area notionally belonged, the pre-Catalan Church is still held to have aimed for separation from Frankish rule almost from its appearance in our sources. The persistence of this idea rests not least on three papal papyri preserved at Vic that appear to record the elevation of Vic to a short-lived metropolitanate, which is usually taken as the third, and lately the fourth, to set up such a local province. Closer examination of these authentic-looking documents however reveals many inconsistencies, and they appear never to have been used to claim such a dignity for Vic after this episode in 970. This paper examines all the evidence for and against the idea of a pre-Catalan archbishopric and finds it more revealing of local infighting and the politics of rival counts than of a proto-nationalist separatism. In the course of doing so, moreover, it raises questions about the uses to which historians have put the evidence of papal documents more widely given what we now know about their production, and tentatively suggests that we must rethink our use of documents that the popes may in many cases not have approved as evidence for papal policies in this period.